STATEMENT OF SOURCE AND APPLICATION OF FUNDS WITHOUT FORMAL WORKING PAPERS. - Mikesell, R. M. (The Accounting Review, 1959)
Abstract The purpose of this article is to describe a method of reducing the time required for preparing a statement of source and application of funds. It consists of substituting two T-accounts for the formal working papers commonly used in source and application of funds preparation. The method is especially useful in examinations because of the great saving of time effected in organizing the information required for the statement. Of the two T-accounts, one is used to accumulate information for determining and explaining the amount of funds provided by operations. The second T-account is used to list funds provided and funds applied, the balance, of course, representing the change in working capital as shown in detail by the statement of working capital changes or determined in some other manner. In preparation of the formal statement of source and application of funds, if time is limited, the student may be allowed to show funds provided by operations as a single figure, since he has already shown the details in his T-account.